The Spin ability of Genetically Modified Acala Cotton Compared with Traditional Acala Cotton - M. El Jack, Kamal; A. Hmed, Azza; A. El Tahir, Hafiz (Gezira Journal of Engineering and Applied Sciences, 2016)
The present study aimed to determine the spin ability of genetically modified BT cotton compared with the traditional cotton, Acala, (Hamid variety) under certain conditions. The procedure applied was to produce the most local commercial counts (8, 12, 16, 20, 26 and 30Ne) from the two types of cotton on rotor open end spinning machine. The machine was adjusted to the same technical variables which parallel the commercial production settings for both types of cotton. The spinning machine was fed with slivers after the second passage of drawing with the Linear density (0.1Ne) for the two types of cotton. The feed speed, delivery speed and the draft were changed with the count change. Laboratory tests and data analysis to the produced yarns have been performed. The change in yarn properties with progressive change in count has been reported. Analysis of the results for the BT cotton and Acala cotton showed that the difference between the two types of yarns strength, R.K.M, was not significant in all the produced counts except count (8Ne) in which the Acala yarns were better in strength. At the same time the Acala yarns elongation except count (30Ne) was significantly better than the BT yarns elongation. Also the results showed that BT cotton, can be operated successfully with the same manufacturing conditions as the Acala cotton. Count (30Ne) was the count limit for both types of cotton since the strength has dropped.